Role and Importance of IGF-1 in Traumatic Brain Injuries. (31st August 2015) - Mangiola, Annunziato; Vigo, Vera; Anile, Carmelo; De Bonis, Pasquale; Marziali, Giammaria; Lofrese, Giorgio
Abstract : It is increasingly affirmed that most of the long-term consequences of TBI are due to molecular and cellular changes occurring during the acute phase of the injury and which may, afterwards, persist or progress. Understanding how to prevent secondary damage and improve outcome in trauma patients, has been always a target of scientific interest. Plans of studies focused their attention on the posttraumatic neuroendocrine dysfunction in order to achieve a correlation between hormone blood level and TBI outcomes. The somatotropic axis (GH and IGF-1) seems to be the most affected, with different alterations between the acute and late phases. IGF-1 plays an important role in brain growth and development, and it is related to repair responses to damage for both the central and peripheral nervous system. The IGF-1 blood levels result prone to decrease during both the early and late phases after TBI. Despite this, experimental studies on animals have shown that the CNS responds to the injury upregulating the expression of IGF-1; thus it appears to be related to the secondary mechanisms of response to posttraumatic damage. We review the mechanisms involving IGF-1 in TBI, analyzing how its expression and metabolism may affect prognosis and outcome in head trauma patients.